2011
DOI: 10.1007/s00198-011-1627-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic difference of clinical vertebral fracture risk

Abstract: SummaryVertebral fractures are the most common osteoporotic fractures. Data on the vertebral fracture risk in Asia remain sparse. This study observed that Hong Kong Chinese and Japanese populations have a less dramatic increase in hip fracture rates associated with age than Caucasians, but the vertebral fracture rates were higher, resulting in a high vertebral-to-hip fracture ratio. As a result, estimation of the absolute fracture risk for Asians may need to be readjusted for the higher clinical vertebral frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 30 publications
4
83
0
Order By: Relevance
“…However, the current study was the first to report the gender-and age-specific incidence rates of clinical vertebral fractures in a Japanese population. The incidence rates of clinical vertebral fractures in this study were higher than those in Sweden or Hong Kong [28,29]. We identified clinical vertebral fracture rates of 381 and 1089 in males and females, respectively, while those in other studies ranged from 225 [29] to 260 [28] and 427 [29] to 916 [28], respectively (per 100,000 person-years).…”
Section: Discussionmentioning
confidence: 48%
“…However, the current study was the first to report the gender-and age-specific incidence rates of clinical vertebral fractures in a Japanese population. The incidence rates of clinical vertebral fractures in this study were higher than those in Sweden or Hong Kong [28,29]. We identified clinical vertebral fracture rates of 381 and 1089 in males and females, respectively, while those in other studies ranged from 225 [29] to 260 [28] and 427 [29] to 916 [28], respectively (per 100,000 person-years).…”
Section: Discussionmentioning
confidence: 48%
“…In addition, it has been reported that Asian populations have a less dramatic increase in hip fracture rates associated with age than Caucasians, but the vertebral fracture rates were higher. (23,24) We found that lumbar bone density T-scores tended to be lower than those of the femoral neck or hip, and the prevalence of osteoporosis was higher at the lumbar spine than the femoral neck or total hip. This may explain the ethnic differences between Asians and Caucasians in vertebral and hip fracture incidence.…”
Section: Discussionmentioning
confidence: 79%
“…The present study showed that a history of osteoporotic fractures was significantly associated with the risk of falls in patients with T2DM independent of age, duration of T2DM, HbA1c level, and other diabetic complications. Moreover, the presence of vertebral fractures, which are known as an independent predictor of future fractures and frequently occurred in Asians including Japanese compared with other ethics [22], was also significantly associated with the risk of falls in this population. These findings suggest that osteoporotic fractures increase the risk of falls, which in turn leads to an increased incidence of fractures.…”
Section: Discussionmentioning
confidence: 83%